EVALUASI KINERJA PELAYANAN TERMINAL BARUGA DI KOTA KENDARI - Rasmida Rasmida; Abdul Kadir; Adris Ade Putra (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2021)
Based on the Minister Regulation No. 132 Year 2015 Regarding the Implementation of Terminal Road Passenger Transport Terminals, namely, motor vehicle bases to arrange arrivals and departures, raise and lower passengers and / / goods, and transport modes. The terminal also has an important role as an element of spatial planning in relation to improving the mobility and efficiency of urban life in a vehicle. The location and facilities of the terminal are the main things that can influence and attract the interest of the public to use the terminal                The criteria for determining the location of the terminal according to the Technical Guidelines for the Construction of the Highway in the City and Inter-City Transport Terminal (Director General of Land Transportation, 1995) has basic considerations, namely in terms of spatial planning, the location of the terminal should be in accordance with the City Development Spatial Plan and should not disturb the environment around it. Factors that need to be considered in determining the location of the terminal include accessibility, namely the level of achievement of ease that can be expressed by physical distance, time or transportation costs      The results showed that the characteristics of the Baruga terminal in the city of kendari have facilities for office buildings, small mosque, public bathrooms and toilets, bus waiting rooms to depart, city transport lounge waiting rooms, Elf lounge waiting rooms, platform ticket sales, ticket office buildings inside the terminal, Retribution building, Information room building and P3K room, Administration room and surveillance room, Vehicle circulation and circulation of people, Public vehicle parking space, Private vehicle parking space, Reserved parking space and 14 buses operating on the Old City - Bungkutoko Harbor ( PP), Kota Lama - Ktr. Governor (PP), PKL Market - Rs. Bahteramas, Bungkutoko Harbor - IAIN Campus (PP), Puwatu - Governor's Office via Jl.Balaikota (PP), Kota Lama - RS. Bahteramas (PP), Puwatu - Kota Lama, Puwatu-SMA 6-SMPN 9-MAN 1 and Puwatu-Al Qalam From the results of the calculation of the Customer Satisfaction Index (CSI) of bus terminal services, the baruga is very small, 0.31% is caused by ineffective and inefficient terminal routes and bus service translators      keywords: terminal, characteristics, service